Generation-Z and travelling interest in Tebing Tinggi - Haya Haratikka; Anita Purba (Journal of Enterprise and Development (JED), 2023)
Purpose — The aim of this research is to examine the interest of Generation-Z in travel by exploring the factors that influence their choice of tourism destination and reasons for traveling.Method — To collect data for this research, a qualitative method was employed whereby an open-ended online questionnaire was distributed to 71 individuals belonging to the Z generation in Tebing Tinggi City. We utilized thematic analysis as the technique to examine and analyze the data collected.Result — We found that Generation-Z has a psychological need for vacations to alleviate the stress caused by their numerous responsibilities. When traveling, they typically choose the closest and most renowned tourist destination in their area, without spending excessive amounts of money. Popular activities for them include searching for picturesque locations, experiencing local cuisine, and camping. To travel affordably and efficiently, Generation-Z often opts for private vehicles such as motorcycles or cars, which enable them to visit multiple places.Contribution — This study contributes to the body of knowledge on Generation-Z travel behavior and has implications for the tourism industry in terms of catering to this demographic's unique preferences and needs.